Electromagnetic characterisation of MR RF coils using the transmission-line modelling method. - Cassidy, P; Grieve, S; Clarke, K; Edwards, D (2002)
The Transmission-Line Modelling (TLM) method is applied to the electromagnetic characterisation of RF coils and samples for magnetic resonance imaging MRI. Theoretical verification was performed using a simple surface coil. Experimental verification was performed using Alderman-Grant and birdcage coils constructed for use on a 7 T micro-imaging system. The modelling method enabled electromagnetic characteristics of frequency response, electromagnetic field generation, energy stored and power loss to be determined. From these parameters, coil resonant modes, B1 field profiles, voltages, currents, quality factor (Q), pi/2 pulse length, and the equivalent lumped-element circuit components of resistance, inductance and capacitance were calculated. Equations are presented that enable a comprehensive electromagnetic characterisation of the RF coil and sample to be achieved based on the results of the TLM simulations. The use of the TLM method is extended to include the design of safe arbitrary multi-nuclear pulse sequences such that the specific absorption rate (SAR) of tissue, and RF coil component safety limits are not exceeded.